How the Dark Triad Affects Counterproductive Work Behaviour (CWB) and Organizational Citizenship Behaviour (OCB) in Israeli Arab Healthcare Organizations - Cohen, Aaron; Abdo, Geries (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2024)
Few studies have examined the relationship between dark triad personality traits and behavioral outcomes in healthcare organizations. Recent literature has called for much more extensive research on this issue because the dark triad can negatively affect healthcare organizations. To this end, we examined how dark triad traits relate to counterproductive work behaviour (CWB) and organizational citizenship behaviour (OCB), as reported by supervisors and nurses. We surveyed Arab nurses in Israel, specifically 267 nurses at Arab hospitals and retirement homes in the North of the country, and obtained a response rate of 57%. We found that CWB (nurse-reported) is positively associated with secondary psychopathy and negatively associated with narcissism. We also found that OCB (nurse-reported) is negatively associated with secondary psychopathy and positively associated with narcissism. Both primary psychopathy and Machiavellianism are weakly associated with CWB and OCB. We conclude that these destructive behaviours are detrimental to organizational effectiveness and might lead to low-quality patient care. They should be addressed by management.